Fracture mechanics based estimation of fatigue lives of laser welded joints. (November 2018) - Goyal, Rakesh; Bogdanov, Sergey; El-zein, Mohamad; Glinka, Grzegorz
Abstract: The conventional joining methods like resistance spot welding and arc welding have several challenges during joining of thin sheets of high strength steel materials. One of the main challenges is that application of these joining methods may result in a severe distortion of welded structure. Therefore, laser welding process has emerged as an alternative joining process which can help mitigate some of these challenges. Lower heat input from laser during the welding process results in a smaller size weld heat affected zone and also in lower overall distortion of the structure. The laser welding process presents an exciting opportunity in designing lighter weight structures. However, the major roadblock to application of laser welding method for large structural parts is that fatigue behavior of laser welded joints is not yet well understood. In order to study the fatigue performance of laser welded joints, detailed experimental and numerical investigations have been carried out and the results are presented in this work. The scope of experimental studies included a large set of coupons with different thicknesses and material combinations. Experimental fatigue test data has been generated for the laser welded joints produced using thin sheets of three grades of high strength steel materials (HSLA and UHSS grades) of several thicknesses (1 mm, 1.6 mm, 2 mm and 3 mm). The fatigue test data sets were obtained at R-ratios of R  = 0.1, R  = 0.2 and R  = 0.3. Another variable introduced into experimental studies was an orientation of laser weld joint with respect to applied loading direction. After fatigue tests were completed, detailed metallurgical investigations have been carried out to understand the failure mechanism and the crack growth behavior in laser welded joints. Based on the observed experimental and numerical studies it was concluded that the strain life based fatigue analysis method which has been successfully applied to study weld toe failures for the arc weld joints is not sufficient for the evaluation of laser welded joints. This is due to the reason that laser welded joints have unique challenges due to weld root crack failures and extremely high stress concentration at the location of crack initiation in the root of laser welded joints between the plates. The fracture mechanics based method has been developed for the fatigue life assessment of laser welded joints. In order to apply this method comprehensive three-dimensional finite element studies were performed. Numerical studies show good correlation of the estimated fatigue lives obtained using proposed fracture mechanics method with the experimental data. Highlights: Fatigue life estimation method of laser welded joints has been proposed. Fatigue test data for the laser welded joints of high strength steel thin sheets at 3 different R-ratios. Failure mechanism of laser welded joints under cyclic loading has been found. The UniGrow fatigue crack growth model based on total fatigue life approach has been utilized. Reasonable correlation with the experimentally obtained fatigue life test data has been shown.